THE CONCEPT OF LAND REGISTRATION SYSTEM IN INDONESIA IN REALIZING LEGAL CERTAINATION - INGGRIANI, SRI; SANTIAGO, FAISAL (Awang Long Law Review, 2020)
The land registration system used in Indonesia is a negative publication system with a positive tendency. In a negative registration system (negative system) with a positive tendency, the government does not guarantee legal certainty for the holder of valid evidence (certificate). The government is also not responsible for the data and information contained in land title certificates. Data and information are considered correct as long as no other party sues. This condition causes various problems, such as the emergence of conflicts and land disputes between various parties in several regions in Indonesia. This study is normative with secondary data as a data source. Data is examined by means of document studies. Data is analyzed qualitatively. The results of the analysis are presented descriptively. The research results stated the concept of land registration system in Indonesia in an effort to realize legal certainty is to land that has been certified for more than 5 years and no one has sued, so the land must be immediately positively positive. This means that there are no more lawsuits that can be filed by other people. Therefore, it is proper for the government to immediately implement the mandate of Article 32 paragraph (2) PP No. 24 of 1997 as an effort to provide legal certainty for land owners. This needs to be done so that the state truly guarantees legal certainty and legal protection as well as an orderly land administration for both certificate holders and third parties who obtain land rights in good faith.